2015
DOI: 10.5603/ep.2015.0062
|View full text |Cite
|
Sign up to set email alerts
|

Wyniki leczenia neurochirurgicznego gruczolaków kortykotropowych przysadki w zespole Nelsona — pułapki terapeutyczne

Abstract: Introduction: Nelson's syndrome (NS) is a rare clinical syndrome caused by an enlarging, aggressive corticotroph pituitary adenoma that can occur following bilateral adrenalectomy performed in the treatment of refractory Cushing's disease (CD). Such tumours respond poorly to currently available therapeutic options, which include surgery, radiotherapy, pharmacotherapy, and chemotherapy. They are a challenging problem in neurosurgical practice. The aim of this work was to evaluate the early and long-term results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In these cases, combined therapy may be the only way to attain partial remission, which was defined by the authors as a distinct improvement in the clinical course of NS, with reduced size of the pituitary tumor and decreased -but still exceeding the upper limit of normal -plasma ACTH levels. Similarly, Zielinski et al, recommend the transsphenoidal approach in the pre-invasive phase and the transcranial approach in invasive tumors (65). Our consensus panel emphasized transsphenoidal surgery as the preferred technique in the majority of the cases, depending mostly on tumor localization and growth direction, similar to the approach in other subtypes of pituitary tumors.…”
Section: Transsphenoidal Vs Transcranial Approachmentioning
confidence: 76%
See 3 more Smart Citations
“…In these cases, combined therapy may be the only way to attain partial remission, which was defined by the authors as a distinct improvement in the clinical course of NS, with reduced size of the pituitary tumor and decreased -but still exceeding the upper limit of normal -plasma ACTH levels. Similarly, Zielinski et al, recommend the transsphenoidal approach in the pre-invasive phase and the transcranial approach in invasive tumors (65). Our consensus panel emphasized transsphenoidal surgery as the preferred technique in the majority of the cases, depending mostly on tumor localization and growth direction, similar to the approach in other subtypes of pituitary tumors.…”
Section: Transsphenoidal Vs Transcranial Approachmentioning
confidence: 76%
“…Wilson and coworkers reported that none of the 10 patients with macroadenomas had normalized plasma ACTH levels after neurosurgery (59). In Zielinski's report, all cases that did not achieve remission after surgery were grade IV tumors (according to the Knosp scale) with infiltration of the cavernous sinus (65,68). The extent of parasellar growth, as measured by the Knosp scale, was established as the main factor influencing the effectiveness of surgical treatment.…”
Section: Remission Rates Of Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Secondary empty sella syndrome may be a consequence of pituitary adenoma apoplexy, neurosurgery, radiotherapy, or pharmacotherapy [58][59][60]. Lymphocytic hypophysitis and Sheehan's syndrome are rare causes of secondary empty sella syndrome.…”
Section: Etiopathogenesismentioning
confidence: 99%